Joint location and power optimisation of femto base stations to improve indoor coverage: a geometric approach. Issue 11 (29th July 2016) - Kundu, Anindita; Sanyal, Salil K.; Misra, Iti Saha
Abstract: Femto base station (FBS) deployment with existing Macro Base Stations improves Quality of Service of end users in dead‐zone while simultaneously increasing co‐channel femto–femto interference. This necessitates judicious planning before FBS deployment. In this paper, a novel geometric approach to model any 3‐D deployment region along with two particle swarm optimisation based joint location and power optimisation algorithms: LOA‐POA and LPOA are proposed. The geometric plan of the deployment region (with multiple multistoried buildings) with 3‐D coordinates of serving‐MBS has been generated and provided as input to LOA‐POA and LPOA, to identify positions and transmission powers of the FBSs required to maximise coverage. For a significantly large deployment region of 1600 sq. m., the LPOA identifies locations and transmission powers of four co‐channel FBSs within 140 s while LOA‐POA identifies the same for five FBSs within 40 s. Simulation exhibits requisite coverage after FBS installation. Comparison of these algorithms has been carried out with existing works considering different wall materials. LPOA is observed to provide most economic solution but with higher convergence time than LOA‐POA. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Solving dead‐zone problem of BWA networks requires planned deployment of Femto base stations. We propose a system, which models any 3‐D region. Further, we propose two PSO‐based joint Location and Power Optimisation Algorithms: LOA‐POA or LPOA. These algorithms identify optimal positions and transmission powers of the FBSs required to enhance coverage. Comparison with recent literatures shows improved power efficiency and unchanged time‐complexity of the proposed LOA‐POA algorithm for the deployment region considered. Simulation results exhibit improved coverage and better power efficiency after installation of the FBSs using LPOA compared with LOA‐POA but with higher computational complexity.